Catatan Studi Evolusi Manajemen Sumberdaya Manusia Strategik - Palupi, Majang (Universitas Muhammadiyah Yogyakarta, 2017)
This study is a short review and concise note of the article Lengnick-Hall et al. (2009) about his article entitled “Strategic human resource management: The evolution of the field.” This study examines the evolution and chronological processes of developing strategic human resource management literature. There are seven themes in strategic human resource management. The study also discusses current and future trend issues in strategic human resource management. Finally, this paper provides a strategic human resource management research note.